Basic College Mathematics (9th Edition)

Published by Pearson
ISBN 10: 0321825535
ISBN 13: 978-0-32182-553-7

Chapter 9 - Basic Algebra - Review Exercises: 65

Answer

$= (-\frac{1}{3})^{2}+(\frac{1}{4})(-\frac{4}{9}) = 0$

Work Step by Step

$= (-\frac{1}{3})^{2}+(\frac{1}{4})(-\frac{4}{9})$ $= (\frac{1}{9})-(\frac{4}{36})$ $= (\frac{1}{9}) - (\frac{1}{9})$ $=0$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.